Development of emergency schedules in renovations of building structures - Dariusz Skorupka; Karol Pochybełko (Archives of Civil Engineering)
Construction projects are characterized by high complexity of the tasks performed. They are planned over a long period of time and are often very technologically complex. All these factors cause various types of disruptions to the construction process very often occur during the construction of buildings. In the theory and practice of construction management, the possibility of such disruptions is called risk factors. Due to the fact that they have a significant impact on the preservation of two basic characteristics of construction, i.e. the time and cost of building the facility, they are subject to intensive research. In other words, the challenge for every construction project is to predict risk factors that may disrupt the construction process. Moreover, their specification and quantification, which allows us to estimate the possible impact of disruptions to the construction process on its time and cost. Various risk analysis methods are used for this purpose. The authors of the article propose the use of emergency schedules. Schedules of this type have great utilitarian advantages. That is, they enable illustrating the quantified impact of risk factors on individual tasks and the entire construction project. The material describes the idea of this type of schedules. An example of developing this type of schedule is also given, based on the example of the renovation of a building structures.